Lignin monomer production integrated into the γ-valerolactone sugar platform1. Issue 9 (26th September 2015) - Luterbacher, Jeremy S.; Azarpira, Ali; Motagamwala, Ali H.; Lu, Fachuang; Ralph, John; Dumesic, James A.
<x xml:space="preserve">Abstract</x> We demonstrate an experimental approach for upgrading lignin that has been isolated from corn stover via biomass fractionation using γ-valerolactone (GVL) as a solvent.